2007
DOI: 10.1560/ijee.53.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Invited Minireview: Restoring Demographic Processes in Translocated Populations: The Case of Collared Lizards in the Missouri Ozarks Using Prescribed Forest Fires

Abstract: Habitat fragmentation is one of the more important contributors to species endangerment, but one form of fragmentation, here called dispersal fragmentation, can often go unobserved for many years after it has occurred. Many species live in naturally fragmented habitats, but the local populations are interconnected genetically and demographically by dispersal through the environmental matrix in which the habitats are embedded. Because of dispersal, the local populations are not truly fragmented evolutionarily o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…Further support for our recommendation to maintain connectivity comes from studies that have demonstrated that whilst hybrid breakdown can occur initially when genetically differentiated populations interbreed, this reduction in fitness is often temporary (Templeton 2001). For the long-term survival of vulnerable populations it is better to maintain high levels of selectable variation via induced dispersal, despite the risk of shortterm negative fitness outcomes (Templeton et al 2007). Thus encouraging moderate rates of dispersal between fragmented populations is the most conservative management strategy overall from a genetic perspective.…”
Section: Discussionmentioning
confidence: 93%
“…Further support for our recommendation to maintain connectivity comes from studies that have demonstrated that whilst hybrid breakdown can occur initially when genetically differentiated populations interbreed, this reduction in fitness is often temporary (Templeton 2001). For the long-term survival of vulnerable populations it is better to maintain high levels of selectable variation via induced dispersal, despite the risk of shortterm negative fitness outcomes (Templeton et al 2007). Thus encouraging moderate rates of dispersal between fragmented populations is the most conservative management strategy overall from a genetic perspective.…”
Section: Discussionmentioning
confidence: 93%
“…Templeton et al (2007) provide a descriptive overview of the response to matrix management in terms of colonization of new glades and a preliminary analysis of dispersal. In this paper, we provide a more comprehensive analysis of dispersal, and show how changes in dispersal rates and patterns induced a dynamic transition from a fragmented population of patchy isolates into a nonequilibrium, expanding metapopulation, and finally into a stable metapopulation with a dynamic balance between local extinction and recolonization.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to identify which specific mechanisms are impacted and why, so that predictions can be improved (Urban et al, 2016) and targeted interventions can be developed. For instance, impeded gene flow in eastern collared lizards (Crotaphytus collaris collaris) inhabiting isolated rocky outcrops was initially addressed by translocating individuals (Templeton, Robertson, Brisson, & Strasburg, 2001), but the underlying demographic issues were only rectified when fire suppression activities were modified to facilitate dispersal between outcrops (Brisson, Strasburg, & Templeton, 2003;Templeton, Neuwald, Brazeal, & Robertson, 2007).…”
mentioning
confidence: 99%